Inovasi Pelayanan Administrasi Kependudukan Melalui Program Seblak (Sertifikat Bayi Lahir, Akta Kelahiran, dan Kartu Keluarga) di RS Dr. Mohammad Zyn - Ummu Adila; Dendy Patrija W; Kresna Adhi Prahmana (Lembaga Pengembangan Kinerja Dosen, 2025)
The SEBLAK program (Birth Certificate, Birth Registration, and Family Card) initiated by RS dr. Mohammad Zyn represents an innovation in digital-based civil registration services, aimed at improving efficiency, effectiveness, and transparency in public services related to population administration. This innovation integrates the processes of data collection, verification, and the issuance of administrative documents automatically through a digital system directly connected to the Department of Population and Civil Registration (Disdukcapil). Consequently, procedures for obtaining documents such as birth certificates and family cards can be carried out more quickly, easily, and without bureaucratic obstacles, while also providing more accurate and reliable data. The overall success of this program is supported by several key factors, including adequate technological infrastructure, continuous training for officers and the community, and effective socialization through various media and community forums. A qualitative approach was used to evaluate the implementation process and its impact on the community and hospital staff. Data were collected through in-depth interviews, observations, and documentation, then analyzed using the Miles and Huberman (1994) model. The results indicate that the implementation of this digital system can significantly reduce the time and costs associated with document processing, improve data accuracy, and strengthen public trust in government services. Beyond operational aspects, the SEBLAK program also positively impacts increasing access to administrative services for communities in remote and hard-to-reach areas. This aligns with the goal of expanding digital services inclusively and reinforcing the role of hospitals as the initial point and center for civil registration services while enhancing community participation in fulfilling their administrative rights. However, challenges remain, including technical infrastructure limitations, a lack of sufficient training for human resources, and the need to improve data security capacity. Therefore, continuous capacity building for human resources and infrastructure development are crucial to ensure the sustainability and success of this program, which can serve as a model for innovative public services that other institutions in Indonesia can adopt.